A Single Bout of Aerobic Exercise Improves Motor Skill Consolidation in Parkinson’s Disease - Steib, Simon; Wanner, Philipp; Adler, Werner; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Frontiers in Aging Neuroscience, 2018)
Background: Motor learning is impaired in Parkinson’s disease (PD), with patients demonstrating deficits in skill acquisition (online learning) and consolidation (offline learning) compared to healthy adults of similar age. Recent studies in young adults suggest that single bouts of aerobic exercise, performed in close temporal proximity to practicing a new motor task, may facilitate motor skill learning. Thus, we aimed at investigating the effects of a single bout of aerobic cycling on online and offline learning in PD patients. Methods: 17 PD patients (Hoehn & Yahr 1 – 2.5, age: 64.4 ± 6.2) participated in this crossover study. Immediately prior to practicing a novel balance task, patients either performed 30 minutes of i) moderate intensity (60 – 70% VO2max) aerobic cycling, or ii) seated rest (order counterbalanced). The task required patients to stabilize a balance platform (stabilometer) in a horizontal position for 30 seconds. For each experimental condition, patients performed 15 acquisition trials, followed by a retention test 24 hours later. We calculated time in balance (platform within ±5° from horizontal) for each trial, and analyzed within- and between-subjects differences in skill acquisition (online learning) and skill retention (offline learning) using mixed repeated-measures ANOVA. Results: We found that the exercise bout had no effect on performance level or online gains during acquisition, despite affecting the time course of skill improvements (larger initial and reduced late skill gains). Aerobic cycling significantly improved offline learning, as reflected by larger 24-hour skill retention compared to the rest condition. Conclusion: Our results suggest that a single bout of moderate-intensity AEX is effective in improving motor skill consolidation in PD patients. Thus, acute exercise may represent an effective strategy to enhance motor memory formation in this population. More work is necessary to understand the underlying mechanisms, the optimal scheduling of exercise, and the applicability to other motor tasks. Further, the potential for patients in later disease stages need to be investigated.